Utilizing Choir as a Collaborative Tool to Foster Student Cooperation - Albina Fincensia Doza; Kanzul Fikri; Ferdinandus Bate Dopo; Dek Ngurah Laba Laksana (Universitas Sulawesi Barat, 2025)
This study explores the role of choir activities in fostering character development and cooperative learning among elementary school students at a Christian school in East Nusa Tenggara. Using a qualitative descriptive approach, data were collected through observations, documentation, and informal interviews with students and teachers involved in the choir program. The findings reveal that choir participation significantly enhances students’ social and emotional development, musical skills, and personal discipline. Students learn cooperation through group rehearsals, where each individual’s voice contributes to the overall harmony, instilling a sense of responsibility and teamwork. Regular practices and public performances help students build confidence, manage emotions, and express themselves creatively. Furthermore, involvement in competitions such as singing competition provides a platform for real-world application of their skills, reinforcing values such as perseverance and collaboration. The choir also serves as an inclusive learning space that supports the growth of various talents and promotes positive peer relationships. The study suggests that choir activities are effective in supporting the holistic development of students and should be integrated more broadly into educational programs to cultivate not only artistic talent but also essential character traits. These findings have implications for the implementation of character-based and culturally responsive education in Indonesian schools.